If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + 8p = -7(8 + -7p) 26 + 8p = (8 * -7 + -7p * -7) 26 + 8p = (-56 + 49p) Solving 26 + 8p = -56 + 49p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-49p' to each side of the equation. 26 + 8p + -49p = -56 + 49p + -49p Combine like terms: 8p + -49p = -41p 26 + -41p = -56 + 49p + -49p Combine like terms: 49p + -49p = 0 26 + -41p = -56 + 0 26 + -41p = -56 Add '-26' to each side of the equation. 26 + -26 + -41p = -56 + -26 Combine like terms: 26 + -26 = 0 0 + -41p = -56 + -26 -41p = -56 + -26 Combine like terms: -56 + -26 = -82 -41p = -82 Divide each side by '-41'. p = 2 Simplifying p = 2
| 5+2y=16 | | 2x^2/1.27^2 | | 6a-1=7(8a+7) | | 3+2y=16 | | (y-9)-(y+8)=3y | | 3/4+1/2=0 | | 2+2y=16 | | 8+8k=-4k+8(1+8k) | | y/3-4=-8 | | 16+19=6+139 | | -23-4x=2+3(-8x+5) | | -2z=0 | | -39x=6 | | 24-8x=6(-8x+4)+6x | | -7(6+3v)=23-8v | | 5c+5=0 | | -91-10=8x+17 | | 6x+4y=1128 | | -1x+2= | | X^2-9x-400=0 | | 104-4x=3x+24 | | 9(11-x)=3(3k-9) | | 6b-4(4+b)=-1+7b | | -19+74=-5x-15 | | 7-6t-5t^2=0 | | 4x-3=3x+6y | | 26+2x=-7x+7(x+2) | | 10x+32x+12= | | -5t=-13-2t | | 4x-11=(-4) | | 6m^2-17m+12=0 | | -3(x+2+x+2)-4=-112 |